THE IMPACT OF PARTNERSHIP PROGRAM TO THE MARKETING CAPABILITIES ON FOSTERED SMEs - Arief, Mohammad (Archives of Business Research, 2020)
The aim of the paper is to exploring the impact of Partnership Program to the Marketing Capabilities On Fostered SMEs. Specifically, this paper focuses to investigate and understand an event or problem that has occurred by collecting various information which is then processed to obtain a solution to the problems uncovered can be resolved. The method of this study used a descriptive qualitative. Our analysis are based on data from 4 Fostered SMEs owners and 1 informant. The result suggest that the Partnership has not been effective against marketing capabilities. Our finding indicated that there’s no training to the fostered SMEs from SOEs to increasing their marketing capability, specially in monitoring and training activity. We argue that its contrary to the regulation concerning the partnership program from government. Therefore, we recommendation for a SOEs to develop and supervise the business activities of Fostered SMEs and training on marketing by focusing on Digital Marketing and Branding. Finaly, this paper also reported for the future research.